Revision of the genus Scleropauropus Silvestri, 1902 (Myriapoda: Pauropoda: Pauropodidae) - Scheller, Ulf (Zootaxa, 2007)
Out of the 31 species currently referred to Scleropauropus Silvestri, 1902, 17 species are removed and placed in other genera, including the new genus Juxtapauropus (of which Scleropauropus (Scleropauropus) crinitus Remy, 1950 is fixed as the type species) and Hystrichopauropus Remy, 1942, originally described as a subgenus of Scleropauropus and raised here to the status of independent genus. The following new combinations are thus proposed: Allopauropus (A.) lemurum (Remy, 1956), A. (Decapauropus) mameti (Remy, 1959), A. (D.) prunilis (Scheller, 1970), A. (D.) squameus (Remy, 1948), A. (D.) quadriramosus (Scheller, 1995), Juxtapauropus angularis (Scheller, 2002), J. beritae (Scheller, 1997), J. carmelus (Scheller, 1999), J. comatus (Remy, 1958), J. crinitus (Remy, 1950), J. dugdalei (Remy, 1956), J. fissus (Scheller, 1994), J. maurusiacus (Remy, 1960), J. rimatus (Scheller, 1997), Pauropus stephani (Remy, 1957), Stylopauropus (Donzelotauropus) christiani (Scheller, 2007), Hystrichopauropus portitor (Remy, 1935). Two new synonymies are established: Scleropauropopsis Remy, 1957 = Pauropus Lubbock, 1867 and Scleropauropoides Remy, 1957 = Decapauropus Remy, 1957.